Brain Metastases from Esophageal Squamous Cell Carcinoma: Clinical Characteristics and Prognosis - Xiao, Linlin; Mowery, Yvonne M.; Czito, Brian G.; Wu, Yajing; Gao, Guangbin; Zhai, Chang; Wang, Jianing; Wang, Jun (Frontiers in Oncology, 2021)
Purpose: Due to the low incidence of intracranial disease among patients with esophageal cancer (EC), optimal management for these patients has not been established. The aim of this real-world study is to describe the clinical characteristics, treatment approaches, and outcomes for esophageal squamous cell carcinoma (ESCC) patients with brain metastases in order to provide a reference for treatment and associated outcomes of these patients. Methods: Patients with ESCC treated at the Fourth Hospital of Hebei Medical University between January 1, 2009 and May 31,2020 were identified in an institutional tumor registry. Patients with brain metastases were included for further analysis and categorized by treatment received. Survival was evaluated by the Kaplan-Meier method and Cox proportional hazards models. Results: Among 19,225 patients with ESCC, 66 (0.34%) were diagnosed with brain metastases. Five patients were treated with surgery, 40 patients were treated with radiotherapy, 10 with systemic therapy alone, and 15 with supportive care alone. The median follow-up time was 7.3 months (95% CI 7.4-11.4). At last follow-up, 59 patients are deceased and 7 patients are alive. Median overall survival (OS) from time of brain metastases diagnosis was 7.6 months (95% CI 5.3-9.9) for all cases. For patients who received locoregional treatment, median OS was 10.9 months (95% CI 7.4-14.3), and survival rates at 6 and 12 months were 75.6% and 37.2%, respectively. For patients without locoregional treatment, median OS was 3.0 months (95% CI 2.5-3.5), and survival rates at 6 and 12 months were 32% and 24%, respectively. OS was significantly improved for patients who received locoregional treatment compared to those treated with systematic treatment alone or supportive care (HR: 0.471, 95% CI 0.276-0.805). The median OS of patients with diagnosis-specific graded prognostic assessment (DS-GPA) score 0-2 was 6.4 months, compared to median OS of 12.3 months for patients with DS-GPA >2 (HR: 0.507, 95% CI 0.283-0.911). Conclusion: Brain metastases are rare in patients with ESCC. DS-GPA score maybe a useful prognostic tool for ESCC patients with brain metastases. Receipt of locoregional treatment including brain surgery and radiotherapy was associated with improved survival.